2002
DOI: 10.1079/sum2002129
|View full text |Cite
|
Sign up to set email alerts
|

Is the productivity of organic farms restricted by the supply of available nitrogen?

Abstract: This paper reviews information from the literature and case studies to investigate whether productivity in organic systems is restricted by the supply of available N during the major phases of crop growth. Organic systems have the potential to supply adequate amounts of available N to meet crop demand through the incorporation of leys, N rich cash crop residues and uncomposted manures. However, this is seldom achieved because leys are only incorporated once every few years and organically produced crop residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…The results confirmed the relevance of N as an important yield-limiting factor in organic farming systems (Torstensson 1998;Berry et al 2002;Möller et al 2006). Evidence that availability of N restricted productivity can be inferred from the low N concentrations of cereal grains, and by the significant improvement of yields and N concentration of crops by introducing external substrates as done in DS ?…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The results confirmed the relevance of N as an important yield-limiting factor in organic farming systems (Torstensson 1998;Berry et al 2002;Möller et al 2006). Evidence that availability of N restricted productivity can be inferred from the low N concentrations of cereal grains, and by the significant improvement of yields and N concentration of crops by introducing external substrates as done in DS ?…”
Section: Discussionsupporting
confidence: 82%
“…FER (Tables 7-9). Berry et al (2002) reported that the concentration of grain N, which coincides with the lowest N supply giving the maximum yield, was stable at about 2.20%. In the present trials the measured grain N concentrations of winter wheat were much lower than 2.20% in all the manure systems based on the exclusive use of solid or liquid farmyard manures or effluents (Table 8), indicating the limitation of winter wheat growth by N availability.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Composting of manures is suggested in organic farming for human health (Berry et al 2002) because of the decrease in phytotoxic substances (Gil, Carballo, and Calvo 2008). Similarly, compost is more intense in macronutrients (Warren et al 2006) and micronutrients (Shah and Anwar 2003), narrow in carbon/N ratio (Zia et al 2003), and free from adverse characteristics (Hara, Ishikawa, and Furuichi 2003).…”
Section: Introductionmentioning
confidence: 97%
“…In organic farming, N is often a scarce and valuable resource (Berry et al 2002;Doltra et al 2011), which is likely to be the case in southeastern Norway. Subsidy policy has led to a separation of livestock and arable productions, resulting in a predominance of stockless arable farming in the southeast.…”
Section: Introductionmentioning
confidence: 99%